J/ψ production as a function of charged particle multiplicity in pp collisions at √s=7 TeV - Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agocs, A. G.; Agostinelli, A.; Salazar, S. Aguilar; Ahammed, Z.; Masoodi, A. Ahmad; Ahmad, N.; et al. (ELSEVIER, 2012)
The ALICE Collaboration reports the measurement of the relative J/psi yield as a function of charged particle pseudorapidity density dN(ch)/d eta in pp collisions at root s = 7 TeV at the LHC. J/psi particles are detected for p(t) > 0, in the rapidity interval vertical bar y vertical bar 0. In the highest multiplicity interval with (dN(ch)/d eta)(bin)) = 24.1, corresponding to four times the minimum bias multiplicity density, an enhancement relative to the minimum bias J/psi yield by a factor of about 5 at 2.5 < y <4 (8 at vertical bar y vertical bar < 0.9) is observed. (C) 2012 CERN. Published by Elsevier B.V. All rights reserved.
Keywords: PROTON-PROTON COLLISIONS; PROMPT; Astronomy & Astrophysics; Physics